Preparation and Performance of Seaweed-Based Polyurethane Membranes Modified with Palm Kernel Shell Activated Carbon for Ammonia Adsorption - Masthura Masthura; Saiful Saiful; Mutia Farida; Salfauqi Nurman; Rofiqul Umam (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Polyurethane membranes derived from renewable resources are increasingly being explored for applications in water treatment, particularly for ammonia adsorption. This study focuses on the development of a seaweed-based polyurethane membrane, synthesized from Gracilaria verrucosa biomass, and modified with palm kernel shell-derived activated carbon (RlgPU5/AC). The membranes were characterized for their mechanical, structural, and thermal properties using techniques such as FTIR, SEM, TGA, and tensile testing. Results showed that the incorporation of activated carbon significantly improved the tensile strength (from 17.65 MPa to 19.94 MPa) and elongation (from 34.9% to 74.2%), while also enhancing the swelling degree and porosity of the membrane. Adsorption experiments revealed that the RlgPU5/AC membrane demonstrated optimal ammonia removal at pH 8, achieving a maximum adsorption capacity of 0.409 mg/g. The adsorption process was governed by the Langmuir isotherm and pseudo-first-order kinetics. Regeneration experiments confirmed that the membrane could be reused with a 69.6% regeneration efficiency using 3 N HCl solution, demonstrating its potential as an effective and sustainable material for ammonia removal in wastewater treatment